Efeitos do ácido 2,4-diclorofenoxiacético isolado e em produto formulado nos parâmetros funcionais de mitocôndrias hepáticas isoladas - Polido, Lucas Roberto Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
A utilização de herbicidas tem aumentado substancialmente, devido ao papel significativo destes no desenvolvimento econômico do setor agrícola. Os herbicidas podem ser categorizados em diferentes classes, com diferentes mecanismos de ação e modos de toxicidade; os mimetizadores de auxina, por exemplo, possuem ação análoga às auxinas, fitormônios presentes nas células vegetais. Considerando que a mitocôndria é uma organela fundamental na manutenção de diversos processos biológicos, como equilíbrio energético e morte celular, este estudo objetiva investigar os mecanismos de toxicidade do ácido 2,4-diclorofenoxiacético (ácido 2,4-D), um mimetizador de auxinas e um dos herbicidas mais utilizados na agricultura, em mitocôndrias hepáticas isoladas. Para essa finalidade, foram avaliados efeitos relacionados à bioenergética e à estrutura de mitocôndrias hepáticas isoladas de ratos Wistar jovens, expostas in vitro às concentrações de 0,4 a 200 µmol/L de ácido 2,4-D isolado e ao produto formulado DMA 806 BR em concentrações equivalentes de ácido 2,4-D. Essa faixa compreende concentrações encontradas no ambiente, para melhor compreensão da relevância ambiental; e altas concentrações, com o intuito de investigar a participação da mitocôndria no mecanismo de toxicidade desses compostos como evento-chave inicial (key event) em correlação com os desfechos finais (outcome pathways) descritos na literatura. Foram avaliados: a formação de espécies reativas de oxigênio ou nitrogênio, a oxidação dos nucleotídeos de piridina e dos grupos sulfidril das proteínas, inchamento por espectrofotometria e por microscopia eletrônica, parâmetros de respiração mitocondrial – razão de controle respiratório (RCR), velocidade dos estados 3 e 4 (V3 e V4) e razão de ADP fosforilado por molécula de oxigênio consumida (ADP/O), potencial de membrana e efluxo de cálcio das membranas em mitocôndrias isoladas. Os mecanismos de toxicidade do ácido 2,4-D e os efeitos de suas formulações devem ser investigados em outros modelos experimentais, para elucidar os principais eventos toxicológicos.

The use of herbicides has increased substantially, due to their significant role in the economic development of the agricultural sector. Herbicides can be categorized into different classes, with different mechanisms of action and modes of toxicity; synthetic auxins, for example, may act as auxins, phytohormones present in plant cells. Considering that mitochondria is an organelle fundamental to the maintenance of several biological processes, such as energy balance and cell death, this study aims to investigate the toxicity mechanisms of 2,4-dichlorophenoxyacetic acid (2,4-D), a synthetic auxin and one of the most widely used herbicides in agriculture, in isolated liver mitochondria. For this purpose, effects related to bioenergetics and the structure of hepatic mitochondria, isolated from young Wistar rats and exposed in vitro to concentrations of 0.4 to 200 µM of isolated 2,4-D and to the formulated product DMA 806 BR in equivalent concentrations of 2,4-D were evaluated. This range of doses comprises concentrations already found in the environment, for a better understanding of environmental relevance; and high concentrations, aiming to investigate the role of mitochondria in the toxicity mechanism of these compounds as a key event, correlating with the final outcome pathways described in the literature. The results show that in vitro exposure of isolated liver mitochondria to up to 200 µM of the tested substances does not induce the formation of reactive oxygen or nitrogen species and does not oxidize pyridine nucleotides, in addition to not oxidizing the sulfhydryl groups of mitochondrial membrane proteins significantly, indicating the absence of redox dysregulation or overload of antioxidant defenses. Spectrophotometry experiments indicated that there was no change in the turbidity of the medium containing isolated mitochondria after exposure, which would reflect mitochondrial swelling; and this observation was corroborated by the analysis of mitochondrial structures by transmission electron microscopy. Additionally, exposure to the evaluated concentrations did not alter mitochondrial respiration parameters – respiratory control ratio (RCR), speed of states 3 and 4 (S3 and S4) and phosphorylated ADP per oxygen molecule consumed ratio (ADP/O). However, concentrations from 100 µM of isolated 2,4-D, higher than those generally found in the environment, were able to dissipate the membrane potential and to induce calcium efflux in isolated mitochondria; while exposure to the tested formulated product was able to do so from 200 µM. Our hypothesis is that, for exposures to concentrations equal to or greater than 100 µM, the initial toxicological effects of 2,4-D on isolated mitochondria are chemical interactions with mitochondrial membranes, considering the presence of important chemical functions such as the carboxyl, which makes it chemically similar to many natural fatty acids, components of lipid membranes; and such as the chlorine atoms present in the ring, which contribute to the polarity and electronegativity of the molecule and can interact with membrane elements, such as phosphates. The toxicity mechanisms of 2,4-D and the effects of its formulations should be further investigated in other experimental models to elucidate the main toxicological events.
Effects of 2,4-dichlorophenoxyacetic acid, isolated and in a formulated product, on the functional parameters of isolated rat liver mitochondria
Keywords: 2,4-D; Mitocôndria; Toxicologia; Agrotóxicos; Patologia; Praguicidas; Mitochondria; Toxicology